Perlindungan Nasabah Terkait Praktik Pembukaan Rahasia Bank Oleh Pegawai Bank Dalam Proses Penegakan Hukum Tindak Pidana Pencucian Uang Dihubungkan Dengan Asas Kepastian Hukum - Sutiawan, Hendrik Agus; Mulyati, Etty; Tajudin, Ijud (UI Scholars Hub, 2018)
Bank secrets are essential elements and logical consequences of the bank's business character as a trust institution. Bank secrecy is a form of legal protection for depositors. The purpose of this study is to know how the protection of customers and how law enforcement against the opening of bank secrets by Bank Employee in the process of investigating money laundering crime connected with the principle of legal certainty. This research method using normative juridical approach method, that is an approach used to know that a law in accordance with applicable provisions. The research specification is analytical descriptive, using qualitative juridical data analysis method